Modelling with stakeholders – Next generation. (March 2016) - Voinov, Alexey; Kolagani, Nagesh; McCall, Michael K.; Glynn, Pierre D.; Kragt, Marit E.; Ostermann, Frank O.; Pierce, Suzanne A.; Ramu, Palaniappan
Abstract: This paper updates and builds on 'Modelling with Stakeholders' Voinov and Bousquet, 2010 which demonstrated the importance of, and demand for, stakeholder participation in resource and environmental modelling. This position paper returns to the concepts of that publication and reviews the progress made since 2010. A new development is the wide introduction and acceptance of social media and web applications, which dramatically changes the context and scale of stakeholder interactions and participation. Technology advances make it easier to incorporate information in interactive formats via visualization and games to augment participatory experiences. Citizens as stakeholders are increasingly demanding to be engaged in planning decisions that affect them and their communities, at scales from local to global. How people interact with and access models and data is rapidly evolving. In turn, this requires changes in how models are built, packaged, and disseminated: citizens are less in awe of experts and external authorities, and they are increasingly aware of their own capabilities to provide inputs to planning processes, including models. The continued acceleration of environmental degradation and natural resource depletion accompanies these societal changes, even as there is a growing acceptance of the need to transition to alternative, possibly very different, life styles. Substantive transitions cannot occur without significant changes in human behaviour and perceptions. The important and diverse roles that models can play in guiding human behaviour, and in disseminating and increasing societal knowledge, are a feature of stakeholder processes today. Graphical abstract: Highlights: Participatory modelling has become mainstream in resource and environmental management. We review recent contributions to participatory environmental modelling to identify the tools, methods and processes applied. Global internet connectivity, social media and crowdsourcing create opportunities for participatory modelling. We suggest structured mechanisms to examine and account for human biases and beliefs in participatory modelling. Advanced visualization tools, gaming, and virtual environments improve communication with stakeholders.